Characteristics of collaborative community college/economic development organization partnerships: a multiple case study - Stegeman, Pamela Lane (Kansas State University, 2021)
Inconsistent prosperity across the country and a dearth of skilled workers for new middle-skills jobs have led to a rise in the importance of local workforce development and a consistent talent pipeline for employers. Over the past few years, the availability of a skilled local workforce has become the top concern of business executives and relocation consultants when evaluating locations for company expansion and economic growth. With over half of all jobs in the U.S. middle-skills jobs, and community colleges the primary educators and trainers of middle-skills workers, the need to marry economic development activity and community colleges is becoming clear. Some areas recognized this need and have taken steps to bring these two important community development endeavors together. Certain forward-looking states have been successful at developing employer-specific training programs and have successfully merged them into their state economic development programs. In these programs, community colleges act as the delivery platforms across the state for these employer training programs. On the local level, some economic development organizations (EDOs) and their local community colleges understand this need to deliver a consistent skilled workforce to business to build economic prosperity. These community colleges and EDOs work together to help local businesses grow and attract new business to expand or diversify the local economy. A number of researchers have examined the work between community colleges, EDOs, and local businesses to improve the local economy. Little has been done to understand what it takes for community colleges and EDOs to attract new businesses to an area. The purpose of this study is to understand the characteristics of the partnership between community colleges and EDOs that have a proven track-record in attracting new businesses to their area. Understanding the elements of successful partnerships may help communities wishing to expand their employer base and diversify their economy. This multiple case study examined community college/EDO partnerships using the lens of Kanter’s (1994) critical success factors for collaborative partnerships to determined commonalities across the partnerships and elements of the community colleges that may have contributed to their success. Participants in this study had a very consistent message on critical success factors for their productive, ongoing relationship: Work together across all critical areas of community development for the good of the community; communicate, collaborate, and trust the partner organization; build respect for and from your partner by delivering on promises, understanding your partner’s struggles, and working in innovative ways that help the partnership deliver on its goals. The commonalities across the partnership in regards to these critical success factors suggest their importance in local business attraction efforts, but it also indicates these critical success factors stretch across all community college/EDO partners employing a variety of economic and community growth tactics, as the participants integrated business attraction efforts with other community development activities. Expanding this research to a broader group of partners across the United States in a quantitative study may help further distinguish the critical success factors in community college/EDO partnerships.
Keywords: Community college; Economic development organizations; Partnerships; Workforce development; Critical success factors